A Didactic Research Project: Service Learning and Extended Reason Methodologies Using a Story Reading - Miró López, Susana; de la Rosa Ruiz, Daniel (Calitatea Vieții, 2024)
This didactic research project aims to demonstrate the positive effects on the training of young people from diverse backgrounds, by using different learning methodologies and conducting joint training sessions. This research analyzes the effects of developing a symbiosis of two didactic methodologies: service learning and extended reason. The sample corresponds to two groups of students: some, second-year university students of the degree in social education from an urban environment, and others, students of a basic vocational training cycle in a rural environment. A methodology was developed consisting of hybrid sessions and a physical meeting with the students, in which a story by Flannery O'Connor was read from a multidisciplinary approach: Literature, Anthropology and Social Responsibility. As first conclusions, it was observed: the application of service learning and extended reason methodologies together offer better results than applied individually. The holistic analysis of the story allows us to delve deeper into topics such as human dignity, the meaning of suffering, love and forgiveness. Stemming from the methodological symbiosis, the young person becomes more interested in their learning, comprehensive training is facilitated and a purpose in education is projected beyond the classroom, pointing to their vocation of social service. Education should encourage the social service of future professionals and help us to recognise the dignity of others.